2012
DOI: 10.1088/1751-8113/45/5/055401
|View full text |Cite
|
Sign up to set email alerts
|

D1-strings in large RR 3-form flux, quantum Nambu geometry and M5-branes in theC-field

Abstract: We consider D1-branes in a RR flux background and show that there is a low energy -large flux double scaling limit where the D1-branes action is dominated by a Chern-Simons-Myers coupling term. As a classical solution to the matrix model, we find a novel quantized geometry characterized by a quantum Nambu 3-bracket. Infinite dimensional representations of the quantum Nambu geometry are constructed which demonstrate that the quantum Nambu geometry is intrinsically different from the ordinary Lie algebra type no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 71 publications
1
17
0
Order By: Relevance
“…More recently it has been suggested that maximally supersymmetric five-dimensional Yang-Mills theory can be used to define the (2, 0) theory in the case of a space-like compactification, including all the Kaluza-Klein modes [11,12]. Other, even more recent, discussions on formulating the dynamics of the (2, 0) theory are [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…More recently it has been suggested that maximally supersymmetric five-dimensional Yang-Mills theory can be used to define the (2, 0) theory in the case of a space-like compactification, including all the Kaluza-Klein modes [11,12]. Other, even more recent, discussions on formulating the dynamics of the (2, 0) theory are [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the inclusion of a constant NSNS B-field in the BPS monopole simple amounts to a constant shift in the Nahm equation. The availability of the generalized Nahm construction may allow one to include a constant C-field in a simple manner and check against the quantum geometry [39,40] obtained from other pictures of the system. We leave this interesting issue for future discussions.…”
Section: Discussionmentioning
confidence: 99%
“…In [26], the logic was reversely applied and it was shown how one can deduce the known form of worldvolume noncommutative geometry of D-branes [27][28][29] from a knowledge of how the B-field modifies the Nahm equation; as well as the noncommutative geometry of M5-brane in a large C-field from a knowledge of how the C-field modifies the Basu-Harvey equation [30]. The found noncommutative geometry takes the form of a quantum Nambu geometry [31]. However there has not been success in reformulating this operatorial geometry in terms of more familiar language of a deformed starproduct.…”
Section: Discussionmentioning
confidence: 99%